THE ROLE OF ONE-STEP SERVICE AND LEARNING CADRES IN STRENGTHENING SERVICES FOR VICTIMS OF VIOLENCE AGAINST WOMEN IN TALANG TINGGI, SELUMA REGENCY - Sucita Yurike; Hajar Gelis Pramudyasmono; Ika Pasca Himawati (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
Violence against women remains a significant concern that necessitates accessible, community-based service models. The One Stop Service and Learning (OSS & L) program, implemented by Cahaya Perempuan Women Crisis Center (WCC) Bengkulu, engages grassroots women cadres as primary agents in delivering integrated support to victims. This study examines the role of OSS & L cadres in enhancing services for women experiencing violence and identifies challenges encountered during program implementation. Employing a qualitative descriptive methodology, data were gathered through in-depth interviews, observation, and documentation with WCC coordinators, OSS & L cadres, and health center stakeholders. The results indicate that cadres are instrumental in community outreach, case identification, initial support, and referral to health and support services, thereby improving access and empowering victims. Nevertheless, challenges persist, including limited cadre capacity, insufficient institutional acceptance, and enduring social stigma rooted in patriarchal norms. The study concludes that OSS & L cadres significantly strengthen victim services through a community-based empowerment approach; however, ongoing capacity building, inter-agency collaboration, and policy support are necessary to ensure program sustainability.